Bridge symptoms of insomnia, obsessive-compulsive symptoms, and depression/anxiety: a network analysis - Shiqi Yuan; Ruiyang Wang; Yongyan Shi; Yixin Zhao; Haojuan Tao; Guowei Wu; Liwen Tan; Xuan Ouyang (BMC Psychiatry)
Abstract Background Insomnia has been associated with obsessive-compulsive disorder (OCD), as well as depression and anxiety. However, their interactions and the influence of depression and anxiety on this relationship remain unclear. We aimed to assess the bridge and central symptoms of the insomnia-obsessive-compulsive (OC) network model and explore the impact of depression and anxiety on these connections. Methods A total of 1,046 patients were included in our study. The severity of insomnia, OC, depression, and anxiety were measured using the Pittsburgh Sleep Quality Index, Yale-Brown Obsessive-Compulsive Scale, Zung’s Self-Rating Anxiety Scale, and Zung’s Self-Rating Depression Scale, respectively. Stability analyses of marginal weights were conducted to assess network robustness. Results The network analysis revealed that compulsive behaviors and low sleep quality were shown to be the most central symptoms in the insomnia-OC network, with compulsive behaviors and daytime dysfunction acting as bridge symptoms. Daytime dysfunction, obsessive thoughts, anxiety and panic were found to be bridge symptoms in the insomnia-OC-anxiety network. In the insomnia-OC-depression network, daytime dysfunction, obsessive thoughts, and rhythm disturbances were possible bridge symptoms. Conclusions Compulsive behaviors and daytime dysfunction were linked to insomnia and OC. In the insomnia-OC-anxiety network, anxiety and panic played a central role, while depressed mood was prominent in the insomnia-OC-depression network model. Targeting compulsive behaviors and improving daytime functioning may help reduce insomnia in individuals with OCD. Additionally, addressing anxiety and panic, and rhythm disturbances may further alleviate the psychological distress in these patients.